2018
DOI: 10.1055/s-0038-1675812
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Location-Sensing Electronic Health Record on Clinician Efficiency and Accuracy: A Pilot Simulation Study

Abstract: Background Through the Health Information Technology for Economic and Clinical Health Act of 2009, the federal government invested $26 billion in electronic health records (EHRs) to improve physician performance and patient safety; however, these systems have not met expectations. One of the cited issues with EHRs is the human–computer interaction, as exhibited by the excessive number of interactions with the interface, which reduces clinician efficiency. In contrast, real-time location systems (RTLS)—technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the EHR literature, evaluating clinician efficiency is often the objective, utilizing the time spent or number of mouse clicks to complete a task to demonstrate the impact of an intervention. 27,28 Using time as a measure is understandable as decreasing the time spent performing EHR tasks can help improve the quality and safety of patient care, 29 improve clinician satisfaction, and allow more patients to be seen. 30 It is also an objective measure that demonstrates a targeted outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the EHR literature, evaluating clinician efficiency is often the objective, utilizing the time spent or number of mouse clicks to complete a task to demonstrate the impact of an intervention. 27,28 Using time as a measure is understandable as decreasing the time spent performing EHR tasks can help improve the quality and safety of patient care, 29 improve clinician satisfaction, and allow more patients to be seen. 30 It is also an objective measure that demonstrates a targeted outcome.…”
Section: Discussionmentioning
confidence: 99%
“…King et al 43 (2018) The impact of a location-sensing electronic health record on clinician efficiency and accuracy: a pilot simulation study. The time taken to locate patients (RTLS-A = 11.9 ± 2.0 s versus RTLS-D = 36.0 ± 5.7 s, P < 0.001), the number of rooms searched to find patients (RTLS-A = 1.0 ± 1.06 versus RTLS-D = 3.8 ± 0.5, P < 0.001), and the number of clicks to access patient data (RTLS-A = 1.0 ± 0.06 versus RTLS-D = 4.1 ± 0.13, P < 0.001) were significantly reduced with RTLS-A relative to RTLS-D.…”
Section: Innovation Technologymentioning
confidence: 99%
“…24,25 King et al demonstrated the utility of an RTLSequipped EMR to improve performance in locating patients and increase physician efficiency interacting with the EMR. 26 Our project demonstrated an effective method to automate components of critical care documentation, which usually falls to the individual physician: the perception of time and proactively documenting that time in the chart.…”
Section: Summary and Interpretationmentioning
confidence: 99%